2014
DOI: 10.1007/s10266-014-0179-9
|View full text |Cite
|
Sign up to set email alerts
|

Inter- and intra-observer agreement on Miller’s classification of gingival tissue recessions

Abstract: Miller's is the most commonly used classification of gingival tissue recessions, defined as the displacement of the soft tissue margin apical to the cemento-enamel junction. However, data on the reliability of this classification are missing so far, although reliability, which reflects the consistency of repeated measurements, is regarded as a prerequisite for judging the utility of a classification. The aim of the present study was to evaluate inter- and intra-observer agreement on Miller's classification of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
3
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 24 publications
1
3
0
2
Order By: Relevance
“…Our data is also in agreement with the findings of Bertl et al 17 in 2015 on the inter- and intra-observer agreement for several parameters, revealing substantial to almost perfect intra-observer agreement in the use of Miller’s classification, (in our study, level of inter-observer agreement was almost perfect). In the study by Bertl et al gingival phenotype and tooth shape were evaluated.…”
Section: Discussionsupporting
confidence: 93%
“…Our data is also in agreement with the findings of Bertl et al 17 in 2015 on the inter- and intra-observer agreement for several parameters, revealing substantial to almost perfect intra-observer agreement in the use of Miller’s classification, (in our study, level of inter-observer agreement was almost perfect). In the study by Bertl et al gingival phenotype and tooth shape were evaluated.…”
Section: Discussionsupporting
confidence: 93%
“…It has a multifactorial etiology that is directly attributed to anatomical, mechanical, and pathological factors, that is, the quantity and quality of the gingival tissues, traumatic brushing habits, and plaque accumulation that causes an inflammatory process 19 . It is predominant in males and affects the vestibular aspect of the teeth 21 . The present case report shows Miller class I recessions, which are characterized by no extension of the gingival margin to the mucogingival line without interdental bone loss 18‐20,22 .…”
Section: Discussionmentioning
confidence: 61%
“…The difference in these results could be due to differences in the method of gingival recession assessment. Bert et al assessed gingival recession defects using photographs, whereas we assessed them using the patients [32].…”
Section: Discussionmentioning
confidence: 99%
“…However, our results are in accordance with those of Mahajan et al, who also demonstrated less reliable agreement using Miller's classification (κ = 0.57-0.68) and inter-rater observations (κ = 0.66). This could be due to the fact that Mahajan also assessed recession defects on the patients and not through assessment using photographs, as done byBert et al [32].…”
Section: Discussionmentioning
confidence: 99%